The relevant anatomical parameters of the internal carotid artery and optic nerve in relation to lateral wall of sphenoid sinus-a MRI study - Zamrah, Suzieta (2013)
The relevant anatomical parameters of the internal carotid artery and optic nerve in relation to lateral wall of sphenoid sinus - a MRI study. Sphenoidal surgery and FESS surgery generally has low risk and complications rate. However the surgeries are technically challenging due to complex relationship of neurovascular structures namely internal carotid artery (ICA) and optic nerve . This study illustrates radiological anatomy relationship of the sphenoid sinus with these neurovascular structures. To evaluate certain anatomical parameters of internal carotid artery and optic nerve in relation to the lateral wall of sphenoid sinus based on modified MRI protocol of pituitary gland. In this prospective study of 30 patients carried out from December 2009 until August 2010, the following modified MRI protocols of pituitary were performed. Sagittal, axial and coronal view in fat suppression sequences using slice thickness of 1. 7 mm and spacing of 0.5 mm were performed. The smallest and largest distance between both ICA were measured on coronal and axial views , and their respective locations were determined for each patient. Indentations of optic nerve or internal carotid artery on sphenoid sinus were also evaluated. Sphenoid sinus pneumatisation pattern was studied. Association between internal carotid artery indentation with age, gender and types of sphenoid sinus pneumatisation were determined. Most common type of sphenoid sinus pneumatisation was sellar type (66.7%), followed by post sellar type (26.7%) and presellar type (6.7%). No concha! type noted. The mean of smallest distance between right and left internal carotid arteries were (7.00 ± 4.66 mm (coronal view) and 6.30 ± 4.70 mm (axial view); in which majority (73.3%) located in cerebral/ supraclinoid segment and 26.7% in cavernous. The mean of largest distances were 28.20 ± 5.90 mm (coronal view) and 28.43 ±5.7 mm (axial view). Of this, 46.7% located in cavernous segment, petrous (40.0 %) and cerebral/supraclinoid (13.3%). Indentations of optic nerve and internal carotid artery were noted in 46.7% and 66.7% of patients respectively. There was significant association between type of sphenoid sinus pneumatisation with internal carotid artery indentation ( p = 0.003). No statistically significant association between internal carotid artery indentation with age and gender. Internal carotid artery and optic nerve indentations were noted in 46.7% and 66.7% of the patients respectively in our study. The smallest distance between right and left internal carotid atiery can be as narrow as 6.30 mm, most commonly located in the cerebral/supraclinoid segment. Both these anatomical variants predispose the structures for injury and should be acknowledged to the surgeon before the surgery.